3D Nanosheet-Assembled CoSe Quasi-Microspheres as Advanced Electrode Materials for Electrochemical Energy Storage. Issue 12 (9th August 2017) - Zhu, Yirong; Chen, Xianhong; Chen, Han; Ji, Xiaobo; Liu, Yong
Abstract : Metal selenides, as a new class of metal chalcogenide, have recently attracted researcher's attention as superior electrode materials for energy storage. In this work, we have prepared the 3D nanosheet-assembled CoSe quasi-microspheres by a facile hydrothermal synthesis route and utilize them as supercapacitor electrode materials for the first time. The resulting 3D nanosheet-assembled CoSe quasi-microspheres manifest superior capacitive properties with a high specific capacitance of 440 F g −1 at 1 A g −1, excellent capacity retention rate of 85.9, 56.4 and 41.4% at 10, 50 and 100 A g −1, and good cycling stability with 102.3 and 96.3% of initial capacity retention rate at 2 and 10 A g −1 over 2000 and 5000 cycles, respectively. The good electrochemical performances can be ascribed to the unique 3D micro-/nanostructure with superior pore-size distribution, relatively large mesopores and exceptional electrical conductivity. The asymmetric supercapacitor is further assembled by employing 3D nanosheet-assembled CoSe quasi-microspheres as the cathode and activated carbon (AC) as the anode, respectively. The CoSe/AC asymmetric device displays a energy density of 17.6 Wh kg −1 at a power density of 684 W kg −1, and maintains 95.5% of its initial capacity at 3 A g −1 over 2000 cycles.